Le communisme chinois. - North, Robert C.; Tranchant, Andrée (Paris : Hachette, 1966)
Bibliotheek François Vercammen
Archief Bert Van Hoorick
Frans
Monografie
Keywords: Kommunistische Partij van China; maoïsme; China